PEMANFAATAN SISTEM INFORMASI GEOGRAFIS BERBASIS WEB (WEBGIS) UNTUK PEMETAAN ASET LAHAN DAN BANGUNAN POLITANI SAMARINDA - Kurniadin, Nia; Prasetya, F. V. Astrolabe Sian; Hadi, Pravasta Kiko Setiawan; Feri, Wawan (Universitas Muhammadiyah Gorontalo, 2023)
Politeknik Pertanian Negeri Samarinda (Politani Samarinda) is one of the vocational colleges in East Kalimantan. Based on the Decree of the Governor of East Kalimantan No. 596/K.45/2020 dated January 21, 2020, the land area of the Politani Samarinda is 305.635 m2. The area of land and buildings on it are assets that need to be collected and mapped to make it easier to monitor, development, and maintain buildings as well as the use of all such buildings. The Web-Based Geographic Information System method is used. The purpose of this research is to create a WebGIS for land and building assets of the Politani Samarinda to facilitate monitoring, planning, maintenance, and use of all buildings. The geographic Information system is used to analyze the distribution and use of land and buildings which are then presented in the form of WebGIS. The research begins with a literature study on all immovable assets in the form of land and buildings belonging to the Politani Samarinda. Data consisting of spatial and non-spatial data on the boundaries of existing land and buildings are collected and processed using QGIS to obtain a map of the distribution of buildings and converted to GeoJSON format. WebGIS code is created and tested and uploaded to WebGIS hosting so that it can be accessed online. The output in this research is the existence of a Geographic Information System for the Politani Samarinda building assets that can be accessed online and can be used to facilitate monitoring, planning, maintenance, and use of all buildings.